The effects of forest therapy on public mental health and circular economy: A policy support model in Japan - Zhang, Shujian; Teng, Junfei; Zeng, Yan; Song, Honglin; Gu, Zhijun (Frontiers in Public Health, 2022)
The world faces an embarrassing situation of increasing health expectancy and deteriorating ecological environment. Forest Therapy can help people improve their mental health and reduce their dependence on medicines. Under the global development trend of increasingly limited resources, it will be the future development direction for mankind to use natural resources to improve physical and mental health and promote circular economy as well. In this regard, Japan has excellent public policies and the basis of national consciousness and has made great achievements. Our article will focus on the analysis of Japanese forest service industry, a new model for the integration of the people and forest and local government policy support for the health functions of forests. We used data from 815 participants of 23 forest therapy pilot bases in Japan and found the obvious effect of forest therapy on improving people's mental health. The economic data of the whole Nagano Prefecture and Iiyama city in Nagano indicated that forest therapy pilot cities with policy support from local government have advantages over other cities in circular economy development. The findings suggest that policy support on forest therapy industry should be diversified and coordinated with extensive means to help societies and enterprises.